The Accident of Accessibility: How the Data of the TEF Creates Neoliberal Subjects. (4th July 2019) - Morrish, Liz
ABSTRACT: In an era of neoliberal reforms, academics in UK universities have become increasingly enmeshed in audit. A new Teaching Excellent Framework (TEF) emerged in 2017 with results determined primarily by proxy data of National Student Survey (NSS) scores, retention data and Longitudinal Educational Outcomes data (LEO). The TEF has been rapidly repurposed in order to shape the behaviour and priorities of both students and academics. The discourse of the TEF legislation, bolstered by studies from HEA/HEPI, assumes the source of inequality of outcome is poor teaching requiring corrective action by universities. Further justification for surveillance and quasi-regulation is borne by appeals to 'value for money' and 'competition'. I argue that what seems to be an arbitrary constellation of proxy data points has in fact been a calculated plan to render universities, staff and students as neoliberal subjects. The accident of accessibility, inasmuch as it overlaps with the neoliberal imperative, has determined which data shall function as Key Performance Indicators (KPIs) and the whole assemblage is cemented by discursive choices which align with neoliberal principles. The Government White Paper Success as a Knowledge Economy, May 2016, forms the text for corpus analysis of keywords, discourses and metaphors. Abbreviation: BIS: HM Government Department of Business, Innovation and Skills; BME: Black and Minority Ethnic; DLHE: Destinations of Leavers from Higher Education; HEI: Higher Education Institution; HERA: Higher Education and Research Act; HESA: Higher Education Statistics Agency; HEA: Higher Education Academy; Hefce: Higher Education Funding Council for England; HEPI: Higher Education Policy Institute; HND: Higher National Diploma; KEF: Knowledge Exchange Framework; KPI: Key Performance Indicator; LEO: Longitudinal Educational Outcomes; NSS: National Student Survey; NUS: national Union of Students; OfS: Office for Students; POLAR: participation of local areas; QAA: Quality Assurance Agency; RAB: Resource Accounting and Budgeting; REF: Research Excellence Framework; ROI: Return on Investment; SDS: Strategically Deployable Shifter; SKE: Success in a Knowledge Economy; TEF: Teaching Excellence and Student Outcomes Framework; WP: Widening Participation